2014
DOI: 10.1167/iovs.14-15647
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing Reveals GUCY2D as a Major Gene Associated With Cone and Cone-Rod Dystrophy in Israel

Abstract: Our study suggested that GUCY2D is a major cause of autosomal dominant cone and cone-rod dystrophies in Israel; this is similar to other Caucasian populations and is in contrast with retinitis pigmentosa (primary rod disease), where the genetic make-up of the Israeli population is distinct from other ethnic groups. We also conclude that WES permits more comprehensive and rapid analyses that can be followed by targeted screens of larger samples to delineate the genetic structure of retinal disease in unique pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Nonetheless, the detection rate is still much lower than the reported 83% of European families interrogated using a similar approach. 43 Other population groups investigated in a comparable manner include Saudi Arabian, 44 Chinese, 45 Thai, 46 and Israeli, 22,47 with detection rates ranging from 49% to 83% and the number of analyzed genes ranging from 60 to 226.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the detection rate is still much lower than the reported 83% of European families interrogated using a similar approach. 43 Other population groups investigated in a comparable manner include Saudi Arabian, 44 Chinese, 45 Thai, 46 and Israeli, 22,47 with detection rates ranging from 49% to 83% and the number of analyzed genes ranging from 60 to 226.…”
Section: Discussionmentioning
confidence: 99%
“…An increased number of mutations are now being identified in different populations using high-throughput methods such as whole-exome sequencing (WES). 21,22 Improved molecular diagnosis in patients is important, given the number of clinical trials and treatments currently under investigation for this group of disorders. 23 We therefore resorted to a comprehensive WES approach, followed by targeted analysis of all reported IRD genes, toward understanding the genetic architecture of IRD in the indigenous SA population.…”
mentioning
confidence: 99%
“…Among the genes linked to CORD6 in multiple genetic studies (34,45,51,52), GUCY2D coding for a human RetGC1 has been found most frequently affected by substitutions in codon 838 replacing , were shown to cause a prominent shift in Ca 2ϩ sensitivity of the cyclase regulation by GCAP1 when heterologously expressed in cultured HEK293 (44 -46). However, the physiological effects of the Arg 838 substitutions in RetGC1 have not been demonstrated in mammalian photoreceptors.…”
Section: The Arg 838 Mutation In Retgc1 Alters Physiology Of Photorecmentioning
confidence: 99%
“…1,2,[5][6][7][8] The previous studies have identified mutations in 17 patients from nine families. The numbers for reports, cases, and mutations are summarized in Table 2.…”
Section: Comparative Analysis Of the Literature Datamentioning
confidence: 99%
“…There have been only six previous reports describing C8orf37 mutations, 1,2,[5][6][7][8] and no clear genotype-phenotype correlations have been described so far. The present study examined a consanguineous family of Moroccan origin including two siblings with early-onset CRD.…”
Section: Introductionmentioning
confidence: 99%